Fire risk assessment of old low-cost residential apartment building ; a perspectives review - Nur Amalina Hanapi,; Jakathisvaran,; Nasrul Arif Ahmad Mahmud, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study is to analyse the fire risk assessment for the old low cost high residential building in Malaysia. This research is conducted through reviewing the methods of study, scoping fire risk important aspects, and analysing the information in order to mitigate a way to do fire risk assessments in old low-cost residential apartment in Malaysia supported by the Uniform Building By-Law (UBBL 1984). As an outcome, this paper will be outlining future expectation of elements to be conducted on improving fire safety in old low-cost high rise residential building and updating its characteristics by imparting more efficient fire risk assessment method for a better safety of fire protection in old low-cost high rise residential building in Malaysia.